KAJIAN SIMBOLISME KULINER MPEK MPEK DALAM INTERAKSI SOSIAL MASYARAKAT PALEMBANG - Misnawati, Desy (Jurnal Vokasi Indonesia, 2019)
Culinary reflects the knowledge, social, economy and culture of the community. Food (food) can be a representation of individual culture and social community. The purpose of this study is to study and describe the picture of the interaction of culinary symbolism in the community of Palembang. The theory used in this study is the theory of symbolic interaction. This study uses a qualitative method with a phenomenological approach. The results of this study describe mpek-mpek culinary is a part that is closely related to consumption activities and social interaction of the people of Palembang. Mpek-mpek is a habitus that is carried out for generations starting from how to choose materials, process, cook, serve and eat it. Through food (food), the students respond to the symbols of life value, the value of work, the value of space or time, the value of relations with nature and the value of relationships with others.